ECNU review of education
ECNU Review of Education (ROE) is an international and open access scholarly journal initiated by the East China Normal University (ECNU) in Shanghai of China. This peer-reviewed journal aims to publish impactful research and innovative articles related to current educational issues in China and abroad. The journal encourages articles using interdisciplinary perspectives and embracing contextual sensitivity. The journal accepts empirical and conceptual papers, integrated research reviews, and scoping reviews, policy reviews, and voices. It is interested in scholarship that theorizes educational experiences in the non-English speaking contexts and timely reviews of important educational researches, policies, and issues. It also welcomes proposals for themed group articles from large-scale research or emerging interests.